Nutritional Status and Eating Habits of Professors of Health Area - Rodrigues-Rodrigues, Thais; Claudia Vieira Gomes, Ana; Rodrigues Neto, Gabriel (International Journal of Sport Studies for Health, 2017)
Objectives: This study aimed to compare the nutritional status and eating habits among teachers of courses in nutrition, nursing, physiotherapy and pharmacy of faculty of medical sciences of Paraíba (FMSPB).Methods: 57 teachers from four courses of FMSPB Participated in the study. All teachers were given specific formation about the study procedures. Weight, height, waist circumference and hip circumference were assessed and a questionnaire called the Food Guide for the Brazilian Population was applied.Results: It was observed that there were no significant differences in the comparative analysis of anthropometric measures, indicators of nutritional status and the risk of cardiovascular disease between courses. It was found that there were significant differences only between nutrition courses vs. pharmacy (P = 0.042) in the comparative analysis of the scores submitted by questionnaire food guide. It was observed that there was no positive correlation between the weight vs. scores food guide and also BMI vs. scores food guide (P > 0.05).Conclusions: It was found that the teachers of nutrition course had a better eating habit than those of the pharmacy course and there was also a significant difference between the healthcare courses for anthropometric measurements, indicators of nutritional status and the risk of cardiovascular disease.